Pengaruh Belanja Daerah Berdasarkan Klasifikasi Ekonomi terhadap Pertumbuhan Ekonomi dan Kesejahteraan Masyarakat di Kabupaten/Kota Provinsi Kalimantan Barat Tahun 2010 - 2015 - Deswantoro, Dwi Bambang; Ismail, Asniar; Hendarmin, Hendarmin (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2017)
This study aims to examine and analyze the influence of local goverment expenditure based on economic classification consisting of personnel expenditure, capital expenditure, goods and services expenditure, grant expenditure and social assistance expenditure on economic growth and social welfare in the regency/city of West Borneo Province. The data in the study used panel data consisting of time series data (2010 -2015) and cross-section data (14 regency/city in West Borneo Province). Hypothesis testing in this study using multiple linear regression and path analysis. The results obtained personnel expenditure, capital expenditure, and social assistance expenditure have a positive and significant influence to economic growth, while grant expenditure has negative and significant influence to economic growth and Goods and services spending has a negative but insignificant influence to economic growth. Subsequently capital expenditure and economic growth have a positive and significant influence to the social welfare while the goods and services have negative and significant influence to the social welfare. Grant expenditure have negative influence and social assistance expenditure has a positive butinsignificant influence to social welfare.